'[T]his world is now thy pilgrimage': William Michael Rossetti's Cognitive Maps of France and Italy. (March 2018) - Sasso, Eleonora
Abstract : This paper takes as its starting point the conceptual metaphor 'life is a journey' as defined byLakoff and Johnson (1980) in order to advance a new reading of William Michael Rossetti's Democratic Sonnets (1907). These political verses may be defined as cognitive-semantic poems, which attest to the centrality of travel in the creation of literary and artistic meaning. Rossetti's Democratic Sonnets is not only a political manifesto against tyranny and oppression, promoting the struggle for liberalism and democracy as embodied by historical figures such as Napoleon, Mazzini, Cavour, and Garibaldi; but it also reproduces Rossetti's real and imagined journeys throughout Europe in the late nineteenth century. This essay examines these references in light of the issues they raise, especially the poet as a traveller and the journey metaphor in poetry. But its central purpose is to re-read Democratic Sonnets as a cognitive map of Rossetti's mental picture of France and Italy. A cognitive map, first theorised by Edward Tolman in the 1940s, is a very personal representation of the environment that we all experience, serving to navigate unfamiliar territory, give direction, and recall information. In terms of cognitive linguistics, Rossetti is a figure whose path is determined by French and Italian landmarks (Paris, the island of St. Helena, the Alps, the Venice Lagoon, Mount Vesuvius, and so forth), which function as reference points for orientation and are tied to the historical events of the Italian Risorgimento. Through his sonnets, Rossetti attempts to build into his work the kind of poetic revolution and sense of history which may only be achieved through encounters with other cultures.